CT/MRI accuracy in detecting and determining preoperative stage of gastric adenocarcinoma in Albania - Malaj, Altin; Bilaj, Fatmir; Shahini, Albana; Miraka, Marjeta (Contemporary Oncology/Współczesna Onkologia, 2017)
Aim of the study : Gastric adenocarcinoma is among most frequent among cancers in Albania. Early detection and staging is helped by imaging methods, including CT and MRI. This study provides evidence on the CT and MRI accuracy in detecting and pre-operative staging of gastric adenocarcinoma in 62 patients in a diagnostic clinic in Albania. The correct staging of the gastric adenocarcinoma helps decide on the next treatment options. Material and methods : Sixty-two patients with gastric adenocarcinoma, confirmed with biopsy, underwent both CT and MRI examination at a clinic in Tirana during same week. Images were reviewed to determine the TNM classifications and staging using the current AJCC guidelines. Data on age, sex, cancer location and differentiation were also collected and analyzed. The accuracy, sensitivity, specificity, positive predictive value and negative predictive value was estimated for both CT and MRI. Results and conclusions : CT has a higher accuracy than MRI (83% vs. 67%) for T1. Accuracy for T2 was the same (74%). Starting with T3 and upwards, MRI has a slightly more accurate ability to detect and stage the gastric adenocarcinoma (T3: 81 vs. 75; T4: 83 vs. 64). Both the CT and MRI abilities to accurately detect the N classification were the same. Regarding the M classification, the MRI has a slightly more accurate ability to detect metastases (M: 83 vs. 64). Clinicians might benefit from using CT whenever suspect gastric adenocarcinoma patients present first. Decision on surgery requires a MRI to rule out metastases.